Golf-related sports injuries of the musculoskeletal system - Moon, H.-W.; Kim, J.-S. (Journal of Exercise Rehabilitation, 2023)
The purpose of this study was to evaluate the characteristics of golf-related musculoskeletal injuries. Golfers were retrospectively surveyed through a 50-item questionnaire. Golfers were divided into injured and noninjured groups according to the presence or absence of musculoskeletal injuries. Of the 208 respondents, 64.0% suffered golf-related injuries, most of which were minor injuries caused by overuse in the early 9.9 weeks. According to the anatomical distribution, the most injured parts were upper limbs, spine, trunk, and lower limbs in that order. As for the distribution by part, the hand and wrist were the most vulnerable, and the lateral elbow damage was 3 times more common than the inner elbow. Self-management for injuries was the most common treatment, and regular preventive exercise accounted for 30% of the injured. Overall, more than half of the respondents suffered from musculoskeletal injuries, self-management was the most common, and less than one-third did regular exercise to prevent injuries. Therefore, active management to prevent golf-related musculoskeletal injuries may be necessary.